IFE PsychologIA (2005)
The importance of logotherapy has been neglected in the clinical practice in Nigeria. This paper raises some important aspects of logotherapy, which have not been taken into consideration. For instance, there is the issue of using knowledge and wisdom in logotherapy. Other issues are the great emphasis of responsibility of the client/patient, especially the encouragement of self-help of individuals and normalization. These important key issues are geared towards the spiritual dimension of individual patients in the clinical practice